Brain Exposure of Two Selective Dual CDK4 and CDK6 Inhibitors and the Antitumor Activity of CDK4 and CDK6 Inhibition in Combination with Temozolomide in an Intracranial Glioblastoma Xenograft - Raub, Thomas J.; Wishart, Graham N.; Kulanthaivel, Palaniappan; Staton, Brian A.; Ajamie, Rose T.; Sawada, Geri A.; Gelbert, Lawrence M.; Shannon, Harlan E.; Sanchez-Martinez, Concepcion; De Dios, Alfonso (Drug metabolism and disposition, 2015)
Effective treatments for primary brain tumors and brain metastases represent a major unmet medical need. Targeting the CDK4/CDK6-cyclin D1-Rb-p16/ink4a pathway using a potent CDK4 and CDK6 kinase inhibitor has potential for treating primary central nervous system tumors such as glioblastoma and some peripheral tumors with high incidence of brain metastases. We compared central nervous system exposures of two orally bioavailable CDK4 and CDK6 inhibitors: abemaciclib, which is currently in advanced clinical development, and palbociclib (IBRANCE; Pfizer), which was recently approved by the U.S. Food and Drug Administration. Abemaciclib antitumor activity was assessed in subcutaneous and orthotopic glioma models alone and in combination with standard of care temozolomide (TMZ). Both inhibitors were substrates for xenobiotic efflux transporters P-glycoprotein and breast cancer resistant protein expressed at the blood-brain barrier. Brain Kp,uu values were less than 0.2 after an equimolar intravenous dose indicative of active efflux but were approximately 10-fold greater for abemaciclib than palbociclib. Kp,uu increased 2.8- and 21-fold, respectively, when similarly dosed in P-gp-deficient mice. Abemaciclib had brain area under the curve (0-24 hours) Kp,uu values of 0.03 in mice and 0.11 in rats after a 30 mg/kg p.o. dose. Orally dosed abemaciclib significantly increased survival in a rat orthotopic U87MG xenograft model compared with vehicle-treated animals, and efficacy coincided with a dose-dependent increase in unbound plasma and brain exposures in excess of the CDK4 and CDK6 Ki values. Abemaciclib increased survival time of intracranial U87MG tumor-bearing rats similar to TMZ, and the combination of abemaciclib and TMZ was additive or greater than additive. These data show that abemaciclib crosses the blood-brain barrier and confirm that both CDK4 and CDK6 inhibitors reach unbound brain levels in rodents that are expected to produce enzyme inhibition; however, abemaciclib brain levels are reached more efficiently at presumably lower doses than palbociclib and are potentially on target for a longer period of time.